(untitled) (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2025)
This research aims to be able to explain and describe the percentage of the use of HOTS (Higher Order Thinking Skills) content in the Javanese High School Examination questions for the 2021/2022 school year in DIY Province, especially in the Yogyakarta City and Bantul Regency areas. This type of research uses descriptive research. The source of the data used is the question script for the Javanese High School Language Examination for the 2021/2022 school year in Yogyakarta City and Bantul Regency. The research data taken is in the form of question data that is only included in the HOTS category questions. The way data is collected is by documentation study. How to analyze data using interactive models are (1) data collection, (2) data reduction, (3) data presentation, and (4) data conclusions while for data validation using validity tests increasing persistence and reliability intrareter and interreter. The results in this research illustrate that the implementation of the HOTS category questions in the Javanese Language School Examination questions of SMA Kota Yogyakarta and Bantul Regency is distributed on the cognitive dimensions C4 (analysis) and C5 (evaluation). Meanwhile, the percentage of distribution of HOTS questions in the Javanese Language School Examination of Yogyakarta City High School amounted to 20% and Bantul Regency amounted to 16%. The comparison results of the implementation of HOTS questions in the School Examination still indicate that they are not proportionate to the demands of implementing HOTS questions that should be and illustrate that the quality of implementation of HOTS questions is still very lacking.